Middle and Late Pleistocene mammal fossils of Arabia and surrounding regions: Implications for biogeography and hominin dispersals - Stewart, M; Louys, J; Price, GJ; Drake, NA; Groucutt, HS; Petraglia, MD (Elsevier, 2017)
Plio-Pleistocene faunal turnovers and their implications for hominin dispersals have recently received considerable attention. Exploration and palaeontological study of faunal exchanges has traditionally centred on East Africa, North Africa and the Levant in Southwest Asia. Despite this attention, considerable debate surrounding the timings, rates, and directions of hominin dispersals remain. Notwithstanding its close geographical proximity to these regions and a landmass of over 3 million km 2 , the Arabian Peninsula has largely been excluded from these discussions, mostly owing to the paucity of its Pleistocene vertebrate record. However, recent palaeoenvironmental studies have demonstrated that Arabia experienced periods of climatic amelioration during the Pleistocene, resulting in the establishment of large, perennial water sources and open-grasslands; conditions vastly different than today. This interpretation is further underpinned by archaeological and palaeontological data, and it is now clear this region is important for understanding faunal and hominin movements between Africa and Eurasia. Examination of the Arabian Middle to Late Pleistocene fossil record in a biogeographical context indicates the composite nature of the Arabian faunal record, with Eurasian and African intrusions present in addition to well-established endemics. Open grassland habitats and taxonomic similarities between Pleistocene Arabia on the one hand, and the Levant and Africa on the other, suggests that hominin dispersal into Arabia did not require significant behavioural and/or technological innovations, while subsequent climatic deterioration likely resulted in hominin retreat/extirpation.